Conducting Classroom Observations : Stallings 'Classroom Snapshot' Observation System for an Electronic Tablet - World Bank Group (World Bank, Washington, DC, 2017)
The “Stallings Classroom Snapshot” instrument, technically called the “Stanford Research Institute Classroom Observation System”, was developed by Professor Jane Stallings for research on the efficiency and quality of basic education teachers in the United States in the 1970s. (Stallings, 1977; Stallings and Mohlman, 1988). The Stallings instrument generates robust quantitative data on the interaction of teachers and students in the classroom, with a high degree of inter-rater reliability (0.8 or higher) among observers with relatively limited training, which makes it suitable for large-scale samples in developing country settings. (Jukes, 2006; Abadzi, 2007; DeStefano et al, 2010; Schuh-Moore et al, 2010). The instrument is language and curriculum-neutral, so results are directly comparable across different types of schools and country contexts, and a growing body of comparative country data from the US and developing countries is available. Use of the Stallings classroom snapshot in more than seven countries in the Latin America and the Caribbean region in recent years has generated a global data base of more than 20,000 different classroom observations in more than 3,600 schools. A public use online database is being created on the World Bank/SIEF (Strategic Impact Evaluation Fund) website. These data provide valuable reference benchmarks for any country or education system that uses the Stallings instrument following the protocol outlined in this guide.